Effects of dietary conjugated linoleic acid at high-fat levels on triacylglycerol regulation in mice - Andreoli, Maria Florencia (2009)
Objective: Our aim was to investigate the effects of dietary conjugated linoleic acid (CLA) athigh-fat (HF) levels on parameters related to triacylglycerol (TG) regulation and some potentialimpacts on liver damage.Methods: Growing mice were fed a control diet (7% corn oil), an HF diet containing 20% corn oil, or an HF diet containing 3% CLA (HF CLA) for 30 d. Tissue and organ weights, plasma and tissue TG levels, and parameters related to their regulation were evaluated. Liver oxidative status was also assessed.Results: Dietary CLA showed detrimental and beneficial effects. CLA added to the HF diet caused hepatomegaly (+32%) and exacerbated the hepatic TG accumulation (+168%) observed with the HF diet without inducing liver damage; however, it significantly reduced plasma TG concentrations (+37%) and normalized muscular TG content. An increase in glutathione was associated with total normalization of liver lipid peroxidation. In addition, HF + CLA caused dystrophy of epididymal fat pads, even when the HF diet had increased the adipose tissue mass (30%). The biochemical mechanisms involved in the regulation of lipid levels were related to reduced (-20%) hepatic very low-density lipoprotein-TG secretion and decreased muscle (-35%) and adipose (-49%) tissue contributions to the removal of plasma TG by lipoprotein lipase enzymes.Conclusion: Examination of CLA at HF levels showed hepatomegaly and exacerbation of lipidaccretion as a negative impact; however, some positive aspects such as hypotriglyceridemia andprotection against oxidative stress were also induced. Even the fat reduction is nutritionallyimportant for weight control; the biochemical mechanisms whereby CLA mediates the potentialeffects could produce undesirable metabolic alterations.